MUNICIPAL WASTEWATER TREATMENT OF BASRAH CITY USING INTERMITTENT CYCLE EXTENDED AERATION SYSTEM (ICEAS) - Sabeeh Al-Rekabi, Wisam; Abdul Kareem Abbas, Abdul Hussain; A. Abbas, Sarmad (Journal of Engineering and Sustainable Development, 2017)
An Intermittent Cycle Extended Aeration System (ICEAS) offers advantages for treating sewage; such as easy operation, process flexibility, and low capital cost. The laboratory bench scale experiments were carried out treating domestic wastewater of Basrah City in fabricated ICEAS reactor of 72 L working volume. The domestic wastewater has the following characteristics (average values) pH= 7.5, Biochemical Oxygen Demand BOD= 200 mg/L, Chemical Oxygen Demand COD= 410 mg/L, Total Phosphorus TP= 7 mg/L, Total Suspended Solid TSS= 272. The aim of this research was to evaluate performance of the ICEAS system for treating domestic wastewater. Experimental results showed that the efficiency of ICEAS reactor to remove COD, Ammonia, TN, and TP were 91%, 83%, 60%, and 72%, while SBR efficiency were 87%, 81%, 58%, 69%, respectively. So, removal efficiency of ICEAS reactor was slightly higher than SBR. Comparison the effluent quality of ICEAS reactor with WHO, European and China discharge standards into surface waters were explained that COD concentration (37 mg/L) was meet to all standards (including Iraqi standard), while Ammonia NH3-N (7.87 mg/L), Total Nitrogen TN (17.16 mg/L) and TP (2.84 mg/L) were to European and China but not meet to WHO standard with slightly differences.